ANALYSIS OF SUSTAINABLE COMPETITIVE ADVANTAGE OF MSMES IN INDONESIA: THE ROLE OF ENTREPRENEURIAL ORIENTATION AND SOCIAL MEDIA MARKETING ADOPTION - Abdurohim, Abdurohim; Setyawati, Amelia; Soehartatiek, Soehartatiek; Wahyudi, Eko Juni; Widarni, Eny Lestari (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2022)
To deal with these business developments, maturity is needed in aspects of its entrepreneurial orientation and the adoption of social media as one of its marketing channels. If these two aspects can be applied properly, this is believed to increase a sustainable competitive advantage. The main objective of this research is to analyze the effect of entrepreneurial orientation and social media marketing on sustainable competitive advantage. The sample in this study amounted to 170 respondents, who were determined by a convenience sampling approach. Data collection uses a questionnaire instrument which is then distributed online. Data analysis using the SPSS application displays data processing results through research instrument testing with validity and reliability tests, multiple regression analysis, coefficient of determination, and hypothesis testing. Based on the results of data analysis, it is concluded that entrepreneurial orientation and social media marketing have a positive and significant effect on sustainable competitive advantage. The research implication explains that MSME actors should be passionate about doing something so that creativity can emerge if you, as an entrepreneur, are passionate about doing or discovering new things. The next implication is recommending that MSME business actors be advised to integrate marketing channels traditionally based on modern marketing